Perilaku Manajemen Laba Berdasarkan Siklus Hidup Perusahaan - Chyntya Lisnawati; Nurzi Sebrina (Universitas Negeri Padang, 2019)
This study aims to examine earnings management behavior is based on the company life cycle. This study is classified as comparative research. The population in this study are manufacturing companies listed on the Indonesian Stock Exchange period of 2013 to 2017. By using purposive sampling method, there were 61 companies as the research’s sample. Earning managements is measured through accrual earnings management and real earning management. Company life cycle is measured using the company cash flow. The type of data used is secondary data obtained from www.idx.co.id and used is descriptive analysis. The results of this study indicate that:1) company in the start up, growth, mature and decline stages tend to use real earning management, 2)there is no decrease in earnings management as the life cycle changes from start up, growth, mature and decline stages